Enhanced Cholinergic Activity Improves Cerebral Blood Flow during Orthostatic Stress - Serrador, Jorge M.; Freeman, Roy (Frontiers in Neurology, 2017)
Cerebral blood flow and consequently orthostatic tolerance when upright depends on dilation of the cerebral vasculature in the face of reduced perfusion pressure associated with the hydrostatic gradient. However, it is still unclear if cholinergic activation plays a role in this dilation. To determine if enhancing central cholinergic activity with the centrally acting acetylcholinesterase inhibitor, physostigmine, would increase cerebral blood flow when upright compared to the peripherally acting acetylcholinesterase inhibitor, neostigmine, or saline. We performed a randomized double-blind dose-ranging study that took place over three days in a hospital based research lab. Eight healthy controls (6 women and 2 men, mean age, 26 years; range 21-33) were given infusions of physostigmine, neostigmine or saline on three different days. 5 min tilts were repeated at baseline (no infusion), Dose 1 (0.2 mcg/kg/min physostigmine; 0.1 mcg/kg/min neostigmine) and Dose 2 (0.6 mcg/kg/min physostigmine or 0.3 mcg/kg/min neostigmine) and placebo (0.9% NaCl). Cerebral blood velocity, beat-to-beat blood pressure and end-tidal CO2 were continuously measured during tilts. Physostigmine (0.6 mcg/kg/min) resulted in higher cerebral blood velocity during tilt (90.5±1.5%) than the equivalent neostigmine (85.5±2.6%) or saline (84.8±1.7%) trials (P<0.05). This increase occurred despite a greater postural hypocapnia, suggesting physostigmine had a direct vasodilatory effect on the cerebral vasculature. Cerebral hypoperfusion induced by repeated tilts was eliminated by infusion of physostigmine not neostigmine. Conclusions and Relevance: This study provides the first evidence that enhancement of central, not peripheral, cholinergic activity attenuates the physiological decrease in cerebral blood flow seen during upright tilt. These data suggest that enhancing central cholinergic activity may improve symptoms in patients with symptomatic orthostatic intolerance.